Injured Older Adults Transported by Emergency Medical Services: One Year Outcomes by POLST Status. (3rd March 2020) - Zive, Dana; Newgard, Craig D.; Lin, Amber; Caughey, Aaron B.; Malveau, Susan; Eckstrom, Elizabeth
Abstract: Background: Advance care planning documents, including Physician Orders for Life-Sustaining Treatment (POLST), are intended to guide care near end of life, particularly in emergency situations. Yet, research on POLST during emergency care is sparse. Methods: A total of 7, 055 injured patients age ≥ 65 years were transported by 8 emergency medical services (EMS) agencies to 23 hospitals in Oregon. We linked multiple data sources to EMS records, including: the Oregon POLST Registry, Medicare claims data, Oregon Trauma Registry, Oregon statewide inpatient data, and Oregon vital statistics records. We describe patient and event characteristics by POLST status at time of 9-1-1 contact, subsequent changes in POLST forms, and mortality to 12 months. Results: Of 7, 055 injured older adults, 1, 412 (20.0%) had a registered POLST form at the time of 911 contact. Among the 1, 412 POLST forms, 390 (27.6%) specified full orders, 585 (41.4%) limited interventions, and 437 (30.9%) comfort measures only. By one year, 2, 471 (35%) patients had completed POLST forms. Among the 4 groups (no POLST, POLST-full orders, POLST-limited intervention, POLST-comfort measures), Injury Severity Scores were similar. Mortality differences were present by 30 days (5.0%, 4.6%, 8.0%, and 13.3%, p < 0.01) and were greater by one year (19.5%, 23.9%, 35.4%, and 46.2%, p < 0.01). Conclusions: Among injured older adults transported by ambulance in Oregon, one in 5 had an active POLST form at the time of 9-1-1 contact, the prevalence of which increased over the following year. Mortality differences by POLST status were evident at 30 days and large by one year. This information could help emergency, trauma, surgical, inpatient, and outpatient clinicians understand how to guide patients through acute injury episodes of care and post-injury follow up.